Risk and tropism of central nervous system (CNS) metastases in patients with stage II and III cutaneous melanoma. Issue 20 (25th August 2022) - Johannet, Paul; Simons, Morgan; Qian, Yingzhi; Azmy, Nadine; Mehnert, Janice M.; Weber, Jeffrey S.; Zhong, Judy; Osman, Iman
Abstract : Background: Recent data suggest that patients with stage III melanoma are at high risk for developing central nervous system (CNS) metastases. Because a subset of patients with stage II melanoma experiences worse survival outcomes than some patients with stage III disease, the authors investigated the risk of CNS metastasis in stage II melanoma to inform surveillance guidelines for this population. Methods: The authors examined clinicopathologic data prospectively collected from 1054 patients who had cutaneous melanoma. The χ 2 test, the cumulative incidence, and Cox multivariable regression analyses were performed to evaluate the association between baseline characteristics and the development of CNS metastases. Results: Patients with stage III melanoma had a higher rate of developing brain metastases than those with stage II melanoma (100 of 468 patients [21.4%] vs. 82 of 586 patients [14.0%], respectively; p =  .002). However, patients who had stage IIC melanoma had a significantly higher rate of isolated first recurrences in the CNS compared with those who had stage III disease (12.1% vs. 3.6%; p  = .002). The risk of ever developing brain metastases was similarly elevated for patients who had stage IIC disease (hazard ratio [HR], 3.16; 95% CI, 1.77–5.66), stage IIIB disease (HR, 2.83; 95% CI, 1.63–4.91), and stage IIIC disease (HR, 2.93; 95% CI, 1.81–4.74), and the risk was highest in patients who had stage IIID disease (HR, 8.59; 95% CI: 4.11–17.97). Conclusions: Patients with stage IIC melanoma are at elevated risk for first recurrence in the CNS. Surveillance strategies that incorporate serial neuroimaging should be considered for these individuals until more accurate predictive markers can be identified. Abstract : Patients with stage IIC melanoma are at particularly high risk for experiencing first recurrences in the central nervous system. Surveillance strategies that incorporate serial neuroimaging should be considered for these individuals until accurate predictive markers of central nervous system metastases can be identified